Leadership in a time of transition: an analogy between post-exilic Juda/Yehud and post-apartheid South-Africa : Daniel F. O'Kennedy (Stellenbosch University) - O'Kennedy, Daniël Francois (Old Testament essays, 2017)
There are certain analogies between the post-exilic community in Judah (or Persian Yehud and post-apartheid South Africa. According to the OT two prominent leaders took responsibility for the rebuilding of post-exilic Judah/Yehud: the governor Zerubbabel and the high priest Joshua (cf. Ezra, Nehemiah, Haggai and Zechariah). Two prominent leaders made a major contribution in post-apartheid South Africa: president Nelson Mandela as political leader and archbishop Desmond Tutu as religious leader. This article will make a comparison between these two different communities and their leaders. The article will briefly discuss the respective leaders and will focus on the following analogies: both communities had an influential political leader and a religious leader; the diarchic model of leadership lasted only a few years in Judah/Yehud and in South Africa; the concept of forgiveness played a significant role in both communities (cf. Zech 3 and the Truth and Reconciliation Commission); there was a temple building process in Judah/Yehud and a process of nation building in South Africa.